2022
DOI: 10.1186/s12884-022-04816-7
|View full text |Cite
|
Sign up to set email alerts
|

“I had so many life-changing decisions I had to make without support”: a qualitative analysis of women’s pregnant and postpartum experiences during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic has posed profound challenges for pregnant patients and their families. Studies conducted early in the pandemic found that pregnant individuals reported increased mental health concerns in response to pandemic-related stress. Many obstetric practices changed their healthcare delivery models, further impacting the experiences of pregnant patients. We conducted a survey study to explore the ways in which COVID-19 impacted the lives of pregnant and newly postpartum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…This may be a product of the health system's ability to successfully pivot to alternative modes of care with minimal disruptions to patient care, based on their prior experience implementing similar programs 17 . Even with the change to virtual visits, analysis of open‐ended responses found that some respondents viewed the flexibility offered by virtual appointments as a benefit 13 …”
Section: Discussionmentioning
confidence: 99%
“…This may be a product of the health system's ability to successfully pivot to alternative modes of care with minimal disruptions to patient care, based on their prior experience implementing similar programs 17 . Even with the change to virtual visits, analysis of open‐ended responses found that some respondents viewed the flexibility offered by virtual appointments as a benefit 13 …”
Section: Discussionmentioning
confidence: 99%
“…As it relates to new problems, the pandemic punctuated the health disparities that exist based on income and race. 10 From a patient perspective, the following were amplified, access issues, underlying health disparities, and access or lack thereof to vaccines. From an industry perspective, workforce shortages, supply chain barriers, and provider fears were noted.…”
Section: Regulatory Bodiesmentioning
confidence: 99%
“…Furthermore, pregnancy was classified as a comorbidity for SARS-CoV-2 disease, which increased the risk of maternal and fetal death by 70% and increased the risk of perinatal complications, and heightened patient and provider anxiety. 10 These stressors have impacted the patient risk for adverse events making the health care risk management perspective imperative for physicians.…”
Section: Regulatory Bodiesmentioning
confidence: 99%
See 2 more Smart Citations